An Examination of Trinidadian Officer's Behavioral Beliefs and Intent to Participate in an International Extension Experience - Amy Harder; Alexa J. Lamm; Wayne Ganpat; James R. Lindner (Journal of International Agricultural and Extension Education, 2011)
Participation in an international extension experience empowers extension professionals to meet the needs of diverse clientele in an increasingly global world. A survey of governmental extension workers in Trinidad was conducted to understand how their behavioral beliefs about an international extension experience influenced their intention to participate in such an experience. Behavioral beliefs can be positively or negatively modified based on an individual’s perceptions of the components (time, location, activities) of a specific international extension experience, so manipulating the components should cause corresponding changes in behavioral beliefs and ultimately intent to participate. This study found positive behavioral beliefs about international extension experience participation are held by Trinidadian extension officers. They are willing to travel to a wide variety of locations and are most interested in acquiring hands-on experience and working one-on-one with another extension professional. The most desirable locations and activities should be integrated into international extension experiences in order to positively influence behavioral beliefs, and thereby intent to participate. Future research is needed to more closely examine the impact of participation on extension officers in Trinidad.
Keywords: extension; training; and development; human resource development; professional development